Spatial and temporal distribution and abundance of two species of Persephona (Decapoda: Brachyura: Leucosiidae) on the southern coast of the state of Sao Paulo, Brazil - Perroca, Julia Fernandes [UNESP]; Herrera, Daphine Ramiro [UNESP]; Costa, Rogerio Caetano da [UNESP] (Revista Biota Neotropica, 2019)
Crabs of the genus Persephona are intensely captured in shrimp fisheries as bycatch in the Cananeia region off the coast of the state of Sao Paulo, Brazil. The analysis of the spatial and temporal distribution of Persephona punctata and Persephona mediterranea could provide information about variation in the abundance of these species, as well as the environmental variables affecting their distribution and the existence of a possible habitat partitioning. Using a shrimp fishery boat equipped with double-rig nets, crabs were monthly captured from July 2012 to June 2014 in seven sites: four in the coastal area adjacent to the Cananeia region and three in the Mar Pequeno estuarine area. The abundances of both species were compared according to spatial (among sites) and temporal (years and seasons) scale distribution. A total of 396 individuals of P. punctata and 64 of P. mediterranea were captured. The abundance of both species was higher in the second sampling year (July 2013-June 2014) and in coastal areas; only one individual of each species was captured in the estuarine area due to the low salinity at this location (approximately 27.7%)). The temperature was the environmental variable that most affected the distribution of both species, which was more abundant in warmer periods. The temporal variation in abundance was modulated by temperature, while salinity modulated the spatial distribution of P. punctata and P. mediterranea. The spatial-temporal distribution of both species differered in Cananeia, pointing to a similar use of the environment's resources.
Keywords: Ecological distribution; abiotic factors; Brachyura; habitat partitioning; bycatch